Learning terminology in the process of training of translators - Амеліна, Світлана (Pedagogy of Higher and Secondary Education, 2013)
Amelina S. N. Learning terminology in the process of training of translators. The article deals with problems of learning terminology in the process of training of future translators. The proposals of foreign scientists on the acquisition of terminological knowledge by students are set out. The need to study the terminology in the practical use of the language is emphasized. Means of studying the terminological vocabulary are provided. The examples for learning interprofessional vocabulary in foreign language classes are shown.